Особливості формування економіко-математичних моделей оцінювання технічного стану основних фондів промислових підприємств за методом капіталізації - Козик, В.В.; Ємельянов, О.Ю.; Колещук, О.Я. (Економіка промисловості, 2011)
Визначено сутність і здійснено класифікацію показників технічного стану основних засобів підприємства. Проведено групування чинників, які зумовлюють зношування основних фондів. Ключові слова: основні засоби, промислові підприємства, економіко-математичні моделі, капіталізація. Определена сущность и осуществлена классификация показателей технического состояния основных средств предприятия. Проведено группирование факторов, которые обусловливают износ основных фондов. Ключевые слова: основные средства, промышленные предприятия, экономико-математические модели, капитализация. The essence and classification of the technical state indicators related to enterprise’s fixed assets are defined. The factors that cause the deterioration of fixed assets are grouped. The necessity of using income-based approach to the evaluation of the residual value of fixed assets is grounded. Economic and mathematical models for assessing the technical state of fixed assets by capitalization method have been built. The features of coming catastrophic depreciation of fixed assets have been identified. Keywords: fixed assets, industrial company, economic and mathematical models, capitalization.